Anti-Ly6G binding and trafficking mediate positive neutrophil selection to unleash the anti-tumor efficacy of radiation therapy. (1st January 2021) - Boivin, Gaël; Ancey, Pierre-Benoit; Vuillefroy de Silly, Romain; Kalambaden, Pradeep; Contat, Caroline; Petit, Benoit; Ollivier, Jonathan; Bourhis, Jean; Meylan, Etienne; Vozenin, Marie-Catherine
ABSTRACT: The anti-Ly6G antibody is used to deplete Ly6G pos neutrophils and study their role in diverse pathologies. However, depletion is never absolute, as Ly6G low neutrophils resistant to depletion rapidly emerge. Studying the functionality of these residual neutrophils is necessary to interpret anti-Ly6G-based experimental designs. In vitro, we found anti-Ly6G binding induced Ly6G internalization, surface Ly6G paucity, and primed the oxidative burst of neutrophils upon TNF α co-stimulation. In vivo, we found neutrophils resistant to anti-Ly6G depletion exhibited anti-neutrophil-cytoplasmic-antibodies. In the pre-clinical Kras Lox-STOP-Lox-G12D/WT ; Trp53 Flox/Flox mouse lung tumor model, abnormal neutrophil accumulation and aging was accompanied with an N2-like SiglecF pos polarization and ly6g downregulation. Consequently, SiglecF pos neutrophils exposed to anti-Ly6G reverted to Ly6G low and were resistant to depletion. Noting that anti-Ly6G mediated neutrophil depletion alone had no anti-tumor effect, we found a long-lasting rate of tumor regression (50%) by combining anti-Ly6G with radiation-therapy, in this model reputed to be refractory to standard anticancer therapies. Mechanistically, anti-Ly6G regulated neutrophil aging while radiation-therapy enhanced the homing of anti-Ly6G-boundSiglecF neg neutrophils to tumors. This anti-tumor effect was recapitulated by G-CSF administration prior to RT and abrogated with an anti-TNFα antibody co-administration. In summary, we report that incomplete depletion of neutrophils using targeted antibodies can intrinsically promote their oxidative activity. This effect depends on antigen/antibody trafficking and can be harnessed locally using select delivery of radiation-therapy to impair tumor progression. This underutilized aspect of immune physiology may be adapted to expand the scope of neutrophil-related research.